Affectivity And Time: Towards A Phenomenology Of Embodied Time-Consciousness - Pokropski Marek (Studies in Logic, Grammar and Rhetoric, 2015)
In the article, I develop some ideas introduced by Edmund Husserl concerning time-consciousness and embodiment. However, I do not discuss the Husserlian account of consciousness of time in its full scope. I focus on the main ideas of the phenomenology of time and the problem of bodily sensations and their role in the constitution of consciousness of time. I argue that time-consciousness is primarily constituted in the dynamic experience of bodily feelings.